Accelerating Ice Loss From Peripheral Glaciers in North Greenland. Issue 12 (16th June 2022) - Khan, Shfaqat A.; Colgan, William; Neumann, Thomas A.; van den Broeke, Michiel R.; Brunt, Kelly M.; Noël, Brice; Bamber, Jonathan L.; Hassan, Javed; Bjørk, Anders A.
Abstract: In recent decades, Greenland's peripheral glaciers have experienced large‐scale mass loss, resulting in a substantial contribution to sea level rise. While their total area of Greenland ice cover is relatively small (4%), their mass loss is disproportionally large compared to the Greenland ice sheet. Satellite altimetry from Ice, Cloud, and land Elevation Satellite (ICESat) and ICESat‐2 shows that mass loss from Greenland's peripheral glaciers increased from 27.2 ± 6.2 Gt/yr (February 2003–October 2009) to 42.3 ± 6.2 Gt/yr (October 2018–December 2021). These relatively small glaciers now constitute 11 ± 2% of Greenland's ice loss and contribute to global sea level rise. In the period October 2018–December 2021, mass loss increased by a factor of four for peripheral glaciers in North Greenland. While peripheral glacier mass loss is widespread, we also observe a complex regional pattern where increases in precipitation at high altitudes have partially counteracted increases in melt at low altitude. Plain Language Summary: The Arctic is warming more rapidly than the rest of the world. This warming has had an especially profound impact on Greenland's ice cover. Only 4% of Greenland's ice cover are small peripheral glaciers that are distinct from the ice sheet proper. Despite comprising this relatively small area, these small peripheral glaciers are responsible for 11% of the ice loss associated with Greenland's recent sea level rise contribution. Using the satellite laser platforms Ice, Cloud, and land Elevation Satellite (ICESat) and ICESat‐2, we estimate that ice loss from these Greenland glaciers increased from 27 ± 6 Gt/yr (2003–2009) to 42 ± 6 Gt/yr (2018–2021). We find that the largest acceleration in ice loss is in North Greenland, where we observe ice loss to increase by a factor of four between 2003 and 2021. In some areas, it appears that recent increases in snowfall at high altitudes have partially counteracted recent increases in melt at low altitudes. While many recent Greenland ice loss assessments have focused on only the ice sheet, the recent sharp increase in ice loss from small peripheral glaciers highlights the importance of accurately monitoring Greenland's small peripheral glaciers. These small peripheral glaciers appear poised to play an outsized role in Greenland ice loss for decades to come. Key Points: Greenland peripheral glacier mass loss increased from 27.2 Gt/yr (February 2003–October 2009) to 42.3 Gt/yr (October 2018–December 2021 Mass loss increased by a factor of four for peripheral glaciers in North Greenland during February 2003–December 2021 Enhanced precipitation in northeast Greenland during October 2018–December 2021 resulted in ice thickening at higher elevations